Touch DNA technique and its utility in Criminal Justice System - Gupta, Dr. Geeta; Gupta, Dr. Yogesh (Journal of Neonatal Surgery, 2025)
DNA analysis or DNA profiling done on the samples available from the crime scenes is considered the most important evidence in present criminal justice system. The type of samples on which this analysis are done are blood, semen, body fluids etc. But lack of this sample and lack of proper quantity can be a problem in solving cases which then are labelled as cold cases. There has been many up gradation and research in DNA profiling and of them the most important is Touch DNA analysis. The advantages of this technique like possibilities of analysis of small quantities of sample, collection of DNA from areas of touch like surfaces, clothes, glasswares, mobiles, personal computers etc. has led to solving cold case and complicated cases. Various techniques of touch DNA have their share of challenges. There is constant research and development in new modalities in touch DNA. In present times throughout the globe touch DNA has generated huge interest. In this review we present the overview of the Touch DNA technique and its utility in criminology navigating almost all the aspects including the latest developments, accuracy, advantages, challenges, implications of global use and future perspectives.